The Tradition of Raising Raket Twins in Paopale Laok Village, Sampang - Andi Alfarisi; Moh. Hilal; Isyaq Maulidan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The purpose of this study is to determine whether the tradition of separating the care of raket twins is valid to be carried out based on Islamic law review based on 'urf theory and Compilation of Islamic Law review. Children born as non-identical twins (raket) have different types of care in Paopale Laok Village, Ketapang Subdistrict, Sampang Regency. Children born as a raket must be separated based on customary beliefs. This is done so that twins who are born are spared from bad effects as has happened in the past. The method used in this research is qualitative research. The approach used is normative empirical. Primary data is obtained directly in the field with the process of interviews and observations and then further analysis is carried out. While secondary data is obtained from literature that is in accordance with this research. The results of this study, based on the review of Islamic law using the theory of 'urf, this tradition is included in the category of 'urf fasid because there are rituals that are contrary to syarak and based on the KHI review the tradition is not justified, because there are children's rights that cannot be fulfilled.